A deposit of goddess plaques at Tissamahārāma: Some preliminary considerations - Walburg, Reinhold (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
During the 1996 excavation campaign at Tissamahārāma / Śrī Lankā a hoard of about 800 so-called goddess or Laksmī plaques were discovered inside a house erected on a brick-built fundament. There was no find receptacle but the items lay strewn loose on the earth covering an area of c. 50 × 40 cm. The specimens were exclusively of the very small size type, which is scarce compared to the normal plaques of double height. Such a large number of small specimens in one hoard are unique for the ancient Ceylonese Fundlandschaft. Due to their outer appearance and the metrological data it becomes, again, evident that these objects are religious tokens and not coins. Evaluating all available information, we probably have to think of ritual downpour(s).